2020
DOI: 10.12688/f1000research.23783.2
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloids in commercial potato varieties traded in Nairobi, Kenya

Abstract: Background: Glycoalkaloids are naturally occurring toxins in potatoes which, at high levels, pose food safety concerns to consumers. Their concentrations in potatoes are dependent on postharvest handling, variety and stress factors tubers are exposed to. Limited information, however, exists on levels of glycoalkaloids in commercially traded potato tubers in Kenya. The current study sought to determine the glycoalkaloid levels in potatoes traded in Nairobi, Kenya.  Methods: Three potato varieties, Shangi, Dutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…As it can be seen in Table 5 , α-chaconine was generally found in a higher percentage (from 45 to 77%) than α-solanine (from 23 to 55%), except in the Vivaldi potato variety, where 55% of α-solanine and 45% of α-chaconine were found. These results are consistent with those of other authors such as Musita et al [ 31 ], who typically found a higher quantity of α-solanine than of α-chaconine. The concentration of α-solanine in the potato peel varied between 143 and 1273 mg/kg DW, while the concentration of α-chaconine varied between 117 and 1742 mg/kg DW.…”
Section: Resultssupporting
confidence: 93%
“…As it can be seen in Table 5 , α-chaconine was generally found in a higher percentage (from 45 to 77%) than α-solanine (from 23 to 55%), except in the Vivaldi potato variety, where 55% of α-solanine and 45% of α-chaconine were found. These results are consistent with those of other authors such as Musita et al [ 31 ], who typically found a higher quantity of α-solanine than of α-chaconine. The concentration of α-solanine in the potato peel varied between 143 and 1273 mg/kg DW, while the concentration of α-chaconine varied between 117 and 1742 mg/kg DW.…”
Section: Resultssupporting
confidence: 93%
“…In our raw samples, α-chaconine was always more abundant than α-solanine but below the prescribed limit (Figure 3A,B, Tables S5 and S6). The analysis conducted by Musita et al [53] suggested that the difference in the amount of the two glycoalkaloids is generally conserved among potato tubers, with α-chaconine always more abundant than α-solanine. On the contrary, the total amount of glycoalkaloids can highly vary between the different varieties [53].…”
Section: Quantitative Analysis Of Glycoalkaloids In Colored and Yello...mentioning
confidence: 99%
“…The analysis conducted by Musita et al [53] suggested that the difference in the amount of the two glycoalkaloids is generally conserved among potato tubers, with α-chaconine always more abundant than α-solanine. On the contrary, the total amount of glycoalkaloids can highly vary between the different varieties [53]. Our results provided evidence that a large contribution to the amount of these alkaloids comes from the peels, confirming data from the literature [54].…”
Section: Quantitative Analysis Of Glycoalkaloids In Colored and Yello...mentioning
confidence: 99%
“…Conversely, plants grown under low-temperature conditions exhibited high sucrose phosphate synthase activity. The temperature rise during tuber maturation also impacts the biosynthesis of steroidal glycoalkaloids (SGA), compounds that are toxic to human health and remain unaffected by cooking [67]. Therefore, the temperature increase not only influences potato crop productivity but also poses risks to human health [68].…”
Section: Tuber Maturationmentioning
confidence: 99%